Use of the “Ilizarov” External Fixator in a Dog - Thommasini, M. D.; Betts, C. W. (Veterinary and Comparative Orthopaedics and Traumatology, 1991)
The “Ilizarov” technique is a new exciting concept for bone repair using a dynamic external fixator. The apparatus has proved to be very useful and beneficial because of the stability afforded the fracture site from three-dimensional fixation while providing a mechanism for incremental spatial adjustment over time. The minimum invasion of bone and soft tissue necessary assures minimal disruptance of osseous blood supply. Small diameter pins (0.8–1.2 mm) make innumerable combinations of assembly possible. The system can be used for repair of simple and comminuted fractures, nonunions and osteomyelitis. It is truly unique in the versatility provided for repair of severe bone malformation, especially when the surrounding soft tissue can not immediately adjust to the desired change in bony alignment. It also has similar advantage when used for bone lengthening.
Keywords: Ilizarov’s external fixator; malformation of bone